Source material for breeding winter bread wheat in the north of the Middle Volga region - I. D. Fadeeva; I. N. Gazizov; A. G. Khakimovа; O. P. Mitrofanova (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. Bread wheat (Triticum aestivum L.), due to significant progress in breeding, has high potential of biological productivity, but its implementation is quite low. To change the situation for the better, it is necessary to increase the resistance of developed cultivars to unfavorable abiotic and biotic factors in the regions of its cultivation. To solve this problem, source material is required. The purpose of this research was to evaluate a set of winter wheat accessions from the VIR collection, and first of all, the newly introduced accessions, and the accessions from the working collection of Kazan Scientific Center of the Russian Academy of Sciences for variability of agronomic traits and stability under the conditions of the north of the Middle Volga region, and to identify sources promising for inclusion in the crossing programs.Materials and methods. A three-year field study of 166 winter bread wheat accessions was carried out. All accessions were assessed for their overwintering and plant and ear productivity traits using the methods developed by VIR and the State Variety Trials. The best accessions, or sources, were selected by comparing them with the reference cv. ‘Kazan 560’, taking into account the quantitative values of such indicators as “general adaptability” (ОАСi ), variance of “specific adaptability” (σ2САСi ) and “relative stability” (Sgi) for each accession according to A. V. Kilchevsky and L. V. Khotyleva.Results and conclusion. Descriptions of winter bread wheat accessions are presented in the context of their agronomic traits. Groups and subgroups of accessions with different trait variability levels were identified. Some accessions with stable levels of trait manifestation exceeded the reference in ear productivity. All of them are promising for wheat breeding programs. It is shown that the group of accessions “weakly changing” over the years of study differs from the group of “moderately/strongly changing” accessions in values of correlations between traits and the number of significant correlations.